Smoking as a health problem: A priority-setting study in a tobacco industry dependent village - Nuzulul Kusuma Putri; Riris Diana Rachmayanti (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Indonesia is one of the most cigarettefriendly countries. The tobacco industry has gained economic dependence both nationally and domestically. Baureno Village in Indonesia has more than half of its population relied their life on the tobacco industry for long time. This study analysed how this high tobacco dependent community considered the smoking behaviour as one of prioritized health problems. Methods: This priority-setting study was conducted in quantitative and qualitative phases sequently. The quantitative data on smoking behaviour were collected on 251 households as the samples. This study captured the twelve healthy family indicators issued by The Indonesia Ministry of Health. Further, this data were brought into two different focus group discussions with community leaders and primary healthcare workers to understand how this community considered smoking as a health problem. Their prespective on prioritized health problem was revealed by performing a prioritysetting analysis. Results: Smoking behaviour in cigarette producing areas is the impact of the economic dependence created by the tobacco industry. Ease of access and weak supervision of cigarette distribution in producing cigarette region caused smoking behaviour to be common place in this community group. Community considered smoking as a bottom priority of health problems, while health workers considered smoking as the second priority out of four identified health problems. Conclusion: Community and health workers have a different prioritized health problems. Education to community should be enhanced to increase their awareness on the health impacts of tobacco smoking.